ASSESSMENT OF ACROSOMAL INTEGRITY OF DOG SPERMATOZOA USING SPERMAC STAINING TECHNIQUE - UMAMAGESWARl, J; JOSEPH, CECILIA; KULASEKAR, K; KALATHARAN, J; SRIDEVl, P (The Indian Journal of Animal Reproduction, 2023)
Semen was collected by digital manipulation from eighteen matured dogs of three different breeds. The sperm rich second fraction of semen samples were diluted, cooled and frozen in programmable freezer at three different cooling rates. In an attempt to monitor any changes occurring to the acrosome during freezing, smears made with fresh semen and with frozen semen at various cooling rates were stained with spermac stain and examined under 400x magnifications. Most acrosomal damage appeared to occur during fast and medium cooling rates than in slow cooling rate of programmable freezing. Further, the use of Spermac stain with slight modification in staining technique in the present study provides simple and accurate assessment of the acrosomal membrane changes in frozen thawed dog spermatozoa.